Rapid test detection of anti-infliximab antibodies: performance comparison with three different immunoassays. (November 2020) - Rocha, Cátia; Lago, Paula; Fernandes, Samuel; Correia, Luís; Portela, Francisco; Vieira, Ana Isabel; Patita, Marta; Arroja, Bruno; Ministro, Paula; Alves, Catarina; Dias, Cláudia Camila; Magro, Fernando
Background and Aims: Therapeutic drug monitoring (TDM) of infliximab (IFX) and anti-infliximab antibodies (ATIs) is essential for treatment optimisation in inflammatory bowel disease (IBD) patients. The aim of this study was to estimate and compare the agreement and accuracy between a new rapid test and three established enzyme-linked immunosorbent assays (ELISAs) to quantify ATIs levels, and to evaluate the impact of exogenous IFX on the performance of these assays. Methods: We analysed 200 serum samples from 57 IBD outpatients in IFX induction or maintenance therapy at six IBD centres in Portugal. ATI levels were quantified using the rapid test Quantum Blue® (QB) Anti-Infliximab (Bühlmann) and three established ELISAs: In-House, Theradiag (Lisa Tracker Anti-Infliximab), and Immundiagnostik (IDKmonitor Infliximab). ATIs were quantified in patients' serum samples and spiked samples with exogenous IFX, based on analytical and clinical cutoffs. Qualitative agreement and accuracy were estimated by Cohen's kappa ( k ) with 95% confidence intervals. Results: ATIs quantification with clinical cutoffs showed a slight agreement between QB rapid test and In-House [ k = 0.163 (0.051–0.276)] and Immundiagnostik [ k = 0.085 (0.000–0.177)]. Regarding IFX/ATIs status, the QB rapid test showed a substantial agreement with Theradiag [ k = 0.808 (0.729–0.888)] and a fair agreement with In-House [ k = 0.343 (0.254–0.431)] and Immundiagnostik [ k = 0.217 (0.138–0.297)]. The QB rapid test could not detect ATI-positive levels in samples with exogenous IFX at 5–300 µg/ml. Interference on ATIs detection was observed at exogenous IFX ⩾30 µg/ml for In-house and Immundiagnostik assays. Conclusion: QB rapid test is only suitable to detect ATI-positive levels in the absence of IFX.